1993
DOI: 10.1104/pp.103.4.1399
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan Endotransglycosylase Activity Increases during Kiwifruit (Actinidia deliciosa) Ripening (Implications for Fruit Softening)

Abstract: l h e activity of xyloglucan endotransglycosylase (XET) was assayed in three tissue zones of kiwifruit (Actinidia deliciosa [A.Chev.] C.F. Liang et A.R. Ferguson var deliciosa cv Hayward) at harvest and at severa1 softening stages following a postharvest ethylene treatment. At harvest, extractable XET activity per unit fresh weight in the inner pericarp (IP) and core tissue was 4.5 and 42 times higher, respectively, than in the outer pericarp (OP).Within 24 h of ethylene treatment there was an increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 17 publications
(21 reference statements)
1
87
0
2
Order By: Relevance
“…However, it is possible that they act at the cellulose/xyloglucan interface at the onset of fruit softening, disrupting a crucial structural component of the wall. A consequence of this activity might also be to increase the extent of wall swelling, allowing increased access of other cell wall-degradative enzymes to their substrates and reducing the degree of physical entanglement of cell wall polymers, as has been suggested to occur in ripening kiwifruit (Redgwell et al, 1992;Redgwell and Fry, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that they act at the cellulose/xyloglucan interface at the onset of fruit softening, disrupting a crucial structural component of the wall. A consequence of this activity might also be to increase the extent of wall swelling, allowing increased access of other cell wall-degradative enzymes to their substrates and reducing the degree of physical entanglement of cell wall polymers, as has been suggested to occur in ripening kiwifruit (Redgwell et al, 1992;Redgwell and Fry, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of evidence has been documented that high XTH enzyme activity and its mRNA level were closely correlated with the elongation zone of stems and roots and in ripening fruits in various plant species [23,26,27,[33][34][35][36][37][38]. Analysis of tobacco plants transformed with an antisense construction of NtXET-1 suggested that the reduction in Nt-XET-1 expression might be coupled with strengthening of cell walls [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly clear that related enzymes are associated with xyloglucan metabolism in primary cell walls. XETs are involved in developmentally regulated xyloglucan metabolism (Nishitani and Tominaga, 1992;Potter and Fry, 1994;Redgwell and Fry, 1993;Schroder et al, 1998;de Silva et al, 1994), and a xyloglucan oligosaccharide-specific α-xylosidase is associated with xyloglucan turnover in elongation growth (Koyama et al, 1983;O'Neil et al, 1989).…”
Section: Introductionmentioning
confidence: 99%